2010
DOI: 10.1002/ijc.25047
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of THY1 as a tumor suppressor gene with antiinvasive activity in nasopharyngeal carcinoma

Abstract: THY1 was previously identified as a candidate tumor suppressor gene (TSG) associated with lymph node metastases in nasopharyngeal carcinoma (NPC) through functional studies. It was identified by oligonucleotide microarray analysis as an interesting differentially expressed gene. However, direct functional evidence is still lacking for THY1 being a TSG in NPC, as in vivo tumorigenicity assays have not been previously reported in our last study of THY1. In this study, a tetracycline-inducible expression vector, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…This loss of tumorigenicity during overexpression of CD90 was attributed to G0/G1 cell cycle arrest in HONE1 cells. When CD90 expression was inhibited by shRNA in HONE1 cells that were made non-tumorigenic, tumorigenicity was restored [60] clearly linking CD90 to a tumor-suppressive role also in nasopharyngeal carcinoma (Fig. 1a).…”
Section: Cd90 Acts As a Tumor Suppressormentioning
confidence: 85%
See 2 more Smart Citations
“…This loss of tumorigenicity during overexpression of CD90 was attributed to G0/G1 cell cycle arrest in HONE1 cells. When CD90 expression was inhibited by shRNA in HONE1 cells that were made non-tumorigenic, tumorigenicity was restored [60] clearly linking CD90 to a tumor-suppressive role also in nasopharyngeal carcinoma (Fig. 1a).…”
Section: Cd90 Acts As a Tumor Suppressormentioning
confidence: 85%
“…When an intact copy of chromosome 11 which carries CD90 gene was introduced into highly tumorigenic HONE1 cells through microcell mediated chromosome method, tumor-forming ability in the mouse was suppressed (14 out of 30 mice) or delayed (16 out of 30 mice) [17]. Similarly, Lung et al in their two separate studies observed that when CD90 expression was re-introduced into HONE1 cells through a tetracycline-inducible system, there was a significant reduction in the colony forming ability of the cells in vitro [59] and suppression of tumor formation in nude mice in vivo (8 out of 18 sites injected did not form tumors) [60]. The number of colonies as well as the colony size was reduced during CD90 expression, and invasion through matrigel was inhibited.…”
Section: Cd90 Acts As a Tumor Suppressormentioning
confidence: 87%
See 1 more Smart Citation
“…35 This has been reported in previous studies in which repression of gene expression by dox is not absolute and leakage of transgene expression, especially in vivo, can occur. 31,36,37 Despite reduction of MMP19 in MMP19 C7 and C14 (ĂŸdox) in vivo, the levels of MMP19 expressed were still sufficient to suppress tumor formation in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…Stable clones were selected using neomycin (11). For CD90 knockdown, 3 pairs of CD90 short hairpin RNA (shRNA) oligonucleotides were designed by BLOCK-iT RNAi designer program, as previously described (12). These oligonucleotides target positions 78-99, 298-117, and 301-321 of the human CD90 cDNA (NM_006288).…”
Section: Cd90 Overexpression and Knockdownmentioning
confidence: 99%